Analysis of contract LIC-004-2022 for the skating rink in the municipality of La Vega Cundinamarca (2023)
The purpose of this essay is to examine contract LIC-004-2022 related to the construction of the skating rink in the municipality of La Vega, Cundinamarca. This project, which began in mid-2022, focuses on the construction and additional works of the aforementioned rink, according to the studies and designs provided. The selection of the contractor was carried out through a public bidding process, and Consorcio Obras Deportivas 2022 was the only bidder, being awarded the contract in June 2022. The public works contract was formalized in July of the same year, establishing an execution term of seven (07) months. The purpose of this analysis is to document the events at all stages of the contract since its inception in January of this year. Special attention is given to the contractual part, since, despite the fact that the work began to be executed in January, it has not yet been completed as of the current date. The main focus of the analysis is to identify the causes and reasons that have generated delays in delivery, exceeding the three (03) months expected, as well as defining the fundamental concepts of contracting and public bidding, highlighting the importance of these in the execution of infrastructure projects, especially focusing on the complexities and challenges encountered during the execution of the contract, highlighting the affectations that led to the need for an extension. It critically examines how these issues could have been anticipated and managed more effectively from the beginning of the process. In addition, the relevance and impact that the construction of the skating rink has for the community of La Vega, Cundinamarca is addressed. The importance of understanding not only the contractual and legal aspects, but also the social and community implications of projects of this nature is emphasized. In summary, the essay provides a comprehensive overview of the public contracting and bidding process, highlighting the lessons learned through the complications experienced during contract execution. In addition, it highlights the significant importance of the construction of the skating rink in improving the quality of life and fostering community well-being in La Vega, Cundinamarca.